A Sketch-based 3D Garment Model Retrieval Algorithm (Journal of Fiber Bioengineering and Informatics, 2013)
With the rapid increase in the number of available 3D garment models, the ability to accurately andeffectively search for 3D garment model is crucial for many applications such as industrial design andengineering, and in areas such as manufacturing. In this paper, a sketch-based 3D garment modelretrieval algorithm is reported. Users can draw their sketch images according to their interest sensations.Then they can retrieve the 3D garment from the 3D garment database. Each garment in database isused to render an associated image to represent it. Then local features are extracted based on Gaborfiltering for each image and the input sketch. The bag of features model is used for vectorizing each imageand the sketch. Then the cosine similarities of each garment with the sketch are computed.Evaluationsare performed to show the retrieval performance ofthe proposed algorithm.
Keywords: Model Retrieval; Sketch-Based Retrieval; 3D Garment Retrieval